STRATEGI METRO TV: MENGHADAPI PERSAINGAN DI INDUSTRI PERTELEVISIAN NASIONAL (SEBUAH STUDI KASUS) - Risa Ayuningtyas; M. Gunawan Alif (Bina Nusantara University, 2009)
Due to numerous TV stations established recently in Indonesia, the competitiveness of the television industry had become very complex. Metro TV, which was started to position itself as a news network, still stood consistently in this high competition. The purpose of this case study research was to describe the Metro TV’s position as a news TV channel in encountering the competition with other TV stations, which had more varieties of programs. By analyzing the available information and being supported by theories, this case study expected to give recommendations to Metro TV. The research methodology used in this case study research was a qualitative research method with an approach and focus on Metro TV as one of the national TV stations. This case study concluded that the positioning strategy of news television had brought Metro TV to its niche market, becoming a distinction as compared to the other televisions. However, this positioning advantage could not produce high revenue as high as that of other general TV stations. Implementing an efficient production cost strategy might be an approach that Metro TV could adopt in order to raise profit and stay in the competitive TV industry since Metro TV had built a strong positioning a news TV in public. The Metro TV brand had been very strongly associated with the first pioneer news TV in Indonesia, which became one of its strengths compared to its other competitors. Through the positioning concept and strategy as a news TV station, Metro TV might be able to continuously keep its consistency to serve the area of SES AB+ audience, who mostly came from the professionals and business people as potential targets of Metro TV satisfying their needs of updated news and information.